Occurrence of chaperonin 60 and chaperonin 10 in primary and secondary bacterial symbionts of aphids: implications for the evolution of an endosymbiotic system in aphids - Fukatsu, T; Ishikawa, H (Journal of molecular evolution, 1993)
All aphids harbor symbiotrophic prokaryotes ("primary symbionts") in a specialized-abdominal cell, the bacteriocyte. Chaperonin 60 (Cpn60, symbionin) and chaperonin 10 (Cpn10), which are high and low molecular weight heatshock proteins, were sought in tissues of more than 60 aphid species. The endosymbionts were compared immunologically and histologically. It was demonstrated that (1) there are two types of aphids in terms of the endosymbiotic system: some with only primary symbionts and others with, in addition, secondary symbionts; (2) the primary symbionts of various aphids are quite similar in morphology whereas the secondary symbionts vary; and (3) irrespective of the aphid species, Cpn60 is abundant in both the primary and secondary symbionts, while Cpn10 is abundant in the secondary symbionts but present in small amounts in the primary ones. Based on these results, we suggest that the primary symbionts have been derived from a prokaryote that was acquired by the common ancestor of aphids whereas the secondary symbionts have been acquired by various aphids independently after divergence of the aphid species. In addition, we point out the possibility that the prokaryotes under intracellular conditions have been subject to some common evolutionary pressures, and as a result, have come to resemble cell organelles.